Pelaporan Corporate Social Responsibility pada Kondisi Covid-19 Terhadap Efisiensi Investasi - Ladina, Pregnandia; Saifi, Muhammad; Imamah, Nur (STIE Malangkucecwara, 2023)
This research aims to analyze the effect of corporate social responsibility (CSR) reporting on investment efficiency with information asymmetry as a mediating variable in Covid-19 conditions. This research was conducted on healthcare companies listed on the IDX in 2020-2021. The research sample consisted of 30 companies with purposive sampling. SmartPLS4 was used to test the data. The research results show that CSR has no significant effect on investment efficiency, but CSR has a significant effect on information asymmetry. In addition, information asymmetry does not mediate the effect of CSR on investment efficiency